2007
DOI: 10.1002/asl.162
|View full text |Cite
|
Sign up to set email alerts
|

Cyclone‐induced mixing does not cool SST in the post‐monsoon north Bay of Bengal

Abstract: High-resolution data from the TRMM satellite shows that sea surface temperature (SST) cools by 3 • C under the tracks of pre-monsoon tropical cyclones in the north Indian Ocean. However, even the strongest post-monsoon cyclones do not cool the open north Bay of Bengal. In this region, a shallow layer of freshwater from river runoff and monsoon rain caps a deep warm layer. Therefore, storm-induced mixing is not deep, and it entrains warm subsurface water. It is possible that the hydrography of the post-monsoon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 25 publications
7
126
1
Order By: Relevance
“…Past studies have suggested a potential role of BLs in TC-induced SST cooling (19) and TC intensification (20)(21)(22). However, the impact of BLs on TC intensification has not been definitively demonstrated or quantified.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Past studies have suggested a potential role of BLs in TC-induced SST cooling (19) and TC intensification (20)(21)(22). However, the impact of BLs on TC intensification has not been definitively demonstrated or quantified.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Water advected by these currents was associated with fresher surface waters (Figure 2e), the development of a barrier layer (Thadathil et al, 2007), and a change in sign of T z . 2006-2008 , respectively (Girishkumar et al, 2013. Strong atmospheric heating during the transition (Figure 2c) was the principal reason for greatly increased nearsurface stratification and the nearly complete isolation of the ocean at 15 m depth from weak surface forcing.…”
Section: Monsoon Mixing Cyclesmentioning
confidence: 99%
“…This warming comes from the fact that the pre-storm temperature structure was negatively stratified, supported by stable salinity stratification. This is not uncommon; subsurface mixing during post-SW monsoon cyclones in the northern BoB have been observed to contribute to SST warming due to the presence of a barrier layer (Sengupta et al, 2008;Neetu et al, 2012). Once mixing eroded through the subsurface warm layer, cooling by turbulent mixing dominated atmospheric cooling during the subsequent 30 hours: J q t = -390 W m -2 compared to J q 0 = -176 W m -2 .…”
Section: Tropical Storm Hudhudmentioning
confidence: 99%
“…easterly waves and tropical wave activity, including Rossby-gravity waves, equatorial Rossby waves, Madden Julian Oscillation (MJO) play an important role in the TC formations (Bessafi and Wheeler 2006;Frank and Roundy 2006). The favorable hydrographic conditions such as formation of stably stratified thick barrier layer in & Yashvant Das yashvantdas@rediffmail.com 1 the upper ocean that acts as barrier to vertical mixing and entrainment cooling induced by TC's leading to an increase in heat fluxes from the ocean into the atmosphere play a dominant role for the enhanced TC activity over BoB during post monsoon seasons (Sprintall and Tomczak 1992;Sengupta et al 2008;Balaguru et al 2012). TC activity in BoB is strongly modulated by the tropical intraseasonal oscillation (ISO) (Yanase et al 2010(Yanase et al , 2012.…”
Section: Introductionmentioning
confidence: 99%